Unilateral perineal hernia in female cat - case report - D.P. Alves; T.L. Risso; T.M. Moreira; K.L.S. Navarro; F.F.P.C. Barros; M.E.S.L. Fernandes; H.J.M. Souza (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objective is to report a clinical surgical case of perineal unilateral hernia in a female feline, neutered, 13-years old, mixed-breed admitted in the “hidden for review” Veterinary Hospital presenting prostration, constipation, volume increase and pain in right perineal region started two weeks ago. On clinical inspection it was possible to visualize a rigid, irreducible and painful increased volume in the right perineal region. Ultrasound showed that the increased volume was a hernia containing the colon. The surgical correction was made with herniorrhaphy. One week after the surgical procedure the patient presented a cutaneous abscess, probably originated from fecal contamination, and it was treated by prolonging the use of systemic antibiotics and cleaning of the site. On 45-days after the surgical procedure the patient did not show signs of pain or discomfort and defecated normally. It is suggested that despite perineal hernias being unusual in females, especially neutered, this disease should be included as a differential diagnosis in animals presenting increase of perineal volume, regardless of sex. The classical technique with sutures was considered fast, with low trauma, unlike other correction techniques, besides being successful, avoiding recurrence of the condition and bringing comfort and well-being to the patient.